Analisis Kinerja Pegawai pada Kantor Kecamatan Dukuh Pakis Kota Surabaya - Gerry Wahyu Berlia; Anggraeny Puspaningtyas (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to analyze the performance of employees at the Dukuh Pakis District Office in Surabaya City in carrying out daily administrative tasks as well as socialization activities with the community. The performance measurement method used refers to the four dimensions of employee performance proposed by Mangkunegara (2004), namely quality of work, discipline in work, initiative, and responsibility. Through observation and interviews, it was found that several obstacles hindered the performance of employees, such as lack of discipline in working hours, mismatch between job descriptions and tasks performed, and low supervision and enforcement of sanctions for violations. Nevertheless, there were good initiatives from some employees and a fairly high level of awareness of their responsibilities. Based on these findings, it is recommended to make improvements in time management, increase supervision and enforcement of discipline, provide training to enhance initiative, and solidify job descriptions to optimize employee performance. It is hoped that with the implementation of these recommendations, the performance of employees at the Dukuh Pakis District Office in Surabaya City can be significantly improved.